ANTHROPOLOGICAL FOUNDATIONS OF THE CONCEPT OF "CRIME" IN HISTORICO-PHILOSOPHICAL DISCOURSE - Kovnierova, I. O. (Anthropological Measurements of Philosophical Research, 2020)
Purpose. The paper considers the establishment of the paradigmatic determinants of the understanding of crime on the basis of fundamental changes in understanding of the essence of a man in ancient, medieval, Renaissance, modern and postmodern philosophy. Theoretical basis. The author determines that the understanding of the concept of crime is possible only in the combination of historical, philosophical, legal and sociological approaches. The interpretation of the essence of this concept dynamics and relevant legal practices is based on structuralist, post-structuralist and hermeneutical methodological principles. Originality. The author has proved that the concept of "crime" is not a constant but a historically variable category whose dynamics of meanings is linked to a change in philosophical anthropological paradigms. Its understanding is primarily related to the interpretation of the essence of a man and the imperatives of his behavior. This allows a new understanding of the philosophical foundations of modern criminology. Conclusions. The article establishes that in the history of Western philosophy, there are five anthropological paradigms that differ in a thorough rethinking of the essence of a man. The first cosmocentric regards man as a microcosm, his soul and actions must be in harmony with the harmony of the Cosmos. The second Theocentric considers a man the image and likeness of God, though he is at the same time burdened with original sin. In the era of early Modernism, the third paradigm, which we called cognitive-centric, becomes dominant, since the essence of a man is reduced primarily to his mind. It gradually changes to the fourth – sociocentric, which focuses on the social essence of a man. However, despite its continued existence in our time, at the end of the XX century, there is a transition to the fifth paradigm – postmodernist, which deconstructs the essence of a man, reducing it to the role of an element of power systems. These paradigms, with a certain synchronicity, create the corresponding concepts of "crime": from violation of polis-space laws to identification with sin, from non-observance of mental and moral standards to social deviance. Contemporary understandings of crime are, for the most part, relativistic and constructivist, which is consistent with the postmodern anthropological paradigm. However, the diversity of interpretations of the concept of "crime" that exists in the current scientific literature needs further comprehension.